From Rehabilitation to Punishment: American Corrections after 1945 - Lux, Erin (Université d'Ottawa / University of Ottawa, 2012)
The incarceration rate in the United States has increased dramatically in the period since 1945. How did the United States move from having stable incarceration rates in line with global norms to the largest system of incarceration in the world? This study examines the political and intellectual aspects of incarceration and theories of criminal justice by looking at the contributions of journalists, intellectuals and policy makers to the debate on whether the purpose of the justice system is rehabilitation, vengeance, deterrence or incapacitation. This thesis finds that justice and the institution of the prison itself are not immutable facts of modern civilization, but are human institutions vulnerable to the influence of politics, culture and current events.
Keywords: history; prisons; American History; Conservatism; Goldwater; incarceration; Nixon; New Right; Johnson; Carter; Ford; Bush; policy; politics; Reagan; United States